Ethnic and age-related fat free mass loss in older Americans: The Third National Health and Nutrition Examination Survey (NHANES III) - Akomolafe Abimbola; Adams Richard G; Bond Vernon; Aliyu Muktar H; Obisesan Thomas O; Rotimi Charles N (BMC, 2005)
Abstract Background Although age-related loss of fat free mass (FFM) is well known, there is paucity of data on national estimates, and on the differential influence of ethnicity on the decline in FFM with increasing age. We determined whether age-related loss in FFM and fat free mass index (FFMI) vary by gender and or ethnicity, using representative data from the Third National Health and Nutrition Examination Survey (NHANES III). Methods Analyses were limited to 5,803 non-institutionalized, non-Hispanic Whites and African Americans (Blacks) over the age of 40 years. Body density was calculated from the sum of 3-skinfolds, and percent body fat estimated from body density. FFM was estimated by subtracting body fat from body weight, while FFMI was defined as FFM (kilograms) divided by the square of body height (meter2). Results Overall FFM and FFMI were significantly higher in black women than white women (P = 0.001; P = 0.001 respectively), but similar in black men compared to white men. Age-related decline in FFM reached significance level earlier in black men (at age 65-69) than white men (at age 70-74), and in black women (at age 70-74) than white women (at age 75-79). Similar decline in FFMI was noted in men and in women. In multivariate analyses, FFM significantly associated with ethnicity (p = 0.012) and with age (p < 0.001) in women, but only with age (p < 0.001) in men. In men and in women, FFMI significantly associated with ethnicity (p < 0.001; p = 0.003 respectively) and with age (p < 0.001; p = 0.004 respectively). Conclusion Age-related loss and decline in FFM and FFMI in older Americans is higher for black men and women, than for white men and women. The development of focused population-based preventive strategies is likely to improve functional independence in the aged.